2021
DOI: 10.1111/joca.12366
|View full text |Cite
|
Sign up to set email alerts
|

Connecting with the future: The role of science fiction movies in helping consumers understand privacy‐technology trade‐offs

Abstract: This article examines the ways in which sci‐fi films help consumers understand the tradeoffs between personal privacy concerns and other societal concerns that arise due to new technologies. Drawing upon media priming theory, the authors present a conceptual framework and accompanying research questions that suggest how priming from a futuristic movie influences consumers sentiment toward technology and privacy, from its release date and throughout its availability on movie streaming services. Through a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Thus, future study may explore the effect of sci-fi engagement in experimental settings to establish the causal effect. For example, a line of studies has employed experimental design the test the effect of sci-fi exposure on acceptance of new technology, privacy concern, and political attitudes ( Appel et al, 2016 ; Jones and Paris, 2018 ; Milne et al, 2021 ). It is also interesting to see whether exposure to sci-fi that portrays all humanity or simply displaying futuristic technology or outer space will elicit IWAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future study may explore the effect of sci-fi engagement in experimental settings to establish the causal effect. For example, a line of studies has employed experimental design the test the effect of sci-fi exposure on acceptance of new technology, privacy concern, and political attitudes ( Appel et al, 2016 ; Jones and Paris, 2018 ; Milne et al, 2021 ). It is also interesting to see whether exposure to sci-fi that portrays all humanity or simply displaying futuristic technology or outer space will elicit IWAH.…”
Section: Discussionmentioning
confidence: 99%
“…Through analyzing the frequency of words related to disease (i.e., epidemics, pandemics, plagues, viruses, and disease) in science fiction magazines, Menadue (2020) found that representations of disease in sci-fi correlated with real-world historical trends, supporting that sci-fi appears to reflect and express contemporary human concerns and interests. Additionally, sci-fi works also convey anxiety about the emerging real-world ecological problems (e.g., climate change, technological hazard, overpopulation; Kitzinger, 2010 ; Otto, 2012 ; Rumpala, 2021 ), show existing social problems that violate human rights (e.g., totalitarian politics, social stratification, technological surveillance; Dongmei and Xu, 2018 ; Jones and Paris, 2018 ; Milne et al, 2021 ), and advocate universal humanitarian values that may help in building global solidarity (e.g., multiculturalism, cosmopolitanism; Addison-Smith, 2005 ; Gunderman, 2020 ). In this regard, sci-fi imaginaries, including both utopian and dystopian versions, might serve as a creative tool for global citizenship education by providing prospective envisioning, and proactive planning for the collective future ( Starkey, 2012 ; Montiel et al, 2018 ; Doyle, 2020 ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Limiting data biases as an element of financial well‐being highlights the seemingly innocuous ways personal data is publicly accessible and thus tracked, curated, and sold among companies that subsequently use that data to profile consumers for marketing purposes. In line with technology and privacy concerns (Milne et al, 2021), this can foster consumer harms. “Big data” scraping and tracking exposes consumers to potentially unscrupulous activities amid hyper‐surveillance (Clarke, 2019; Darmody & Zwick, 2020).…”
Section: Implications For Financial Well‐being and Policymentioning
confidence: 99%
“…People pay more attention to visual effects and ignore the existence value of culture itself. Movies convey themes through audio-visual language [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%